Greenhouse Gas Emission Impact of Autonomous Vehicle Introduction in an Urban Network. Issue 5 (May 2019) - Conlon, James; Lin, Jane
This study attempts to quantify the change in carbon dioxide (CO2 ) emissions resulting from autonomous vehicle (AV) introduction in a congested urban network. An integrated traffic microsimulation and emission model is introduced, described, and used to estimate emissions for different AV penetration scenarios ranging from 0% to 100%. AVs show potential to reduce total CO2 emissions at a network scale, approaching 4% reduction at full autonomy, assuming the same fuel technology in AV as in today's fleet. Furthermore, it is found that this reduction is sensitive to the penetration ratio of AVs, and is greatest at full AV penetration; AV penetration may generate greater total vehicular CO2 emissions than 0% AV penetration does, contrary to popular belief. This may be because of the heterogeneity in a mixed traffic environment of human-driven vehicles (HDVs) and AVs, as well as the complex interaction between HDVs and AVs that is not yet fully understood.